2021
DOI: 10.3390/nu13093176
|View full text |Cite
|
Sign up to set email alerts
|

Energy Achievement Rate Is an Independent Factor Associated with Intensive Care Unit Mortality in High-Nutritional-Risk Patients with Acute Respiratory Distress Syndrome Requiring Prolonged Prone Positioning Therapy

Abstract: Early enteral nutrition (EN) and a nutrition target >60% are recommended for patients in the intensive care unit (ICU), even for those with acute respiratory distress syndrome (ARDS). Prolonged prone positioning (PP) therapy (>48 h) is the rescue therapy of ARDS, but it may worsen the feeding status because it requires the heavy sedation and total paralysis of patients. Our previous studies demonstrated that energy achievement rate (EAR) >65% was a good prognostic factor in ICU. However, its impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A retrospective study of 79 patients who were critically ill with moderate‐to‐severe ARDS without COVID‐19 receiving PP therapy within the first 3 days of ICU admission also demonstrated lower EAR during this period in comparison with the following 4 days without PP (42.0% vs 64.5%). The low EAR observed in this study, regardless of the PP position, may have been influenced by the severity of patients at ICU admission (APACHE II median = 31 and SOFA median = 10) 12 . Retrospective data collection precluded us from evaluating the EAR, considering the delivered energy instead of the prescribed energy.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A retrospective study of 79 patients who were critically ill with moderate‐to‐severe ARDS without COVID‐19 receiving PP therapy within the first 3 days of ICU admission also demonstrated lower EAR during this period in comparison with the following 4 days without PP (42.0% vs 64.5%). The low EAR observed in this study, regardless of the PP position, may have been influenced by the severity of patients at ICU admission (APACHE II median = 31 and SOFA median = 10) 12 . Retrospective data collection precluded us from evaluating the EAR, considering the delivered energy instead of the prescribed energy.…”
Section: Discussionmentioning
confidence: 88%
“…The low EAR observed in this study, regardless of the PP position, may have been influenced by the severity of patients at ICU admission (APACHE II median = 31 and SOFA median = 10). 12 Retrospective data collection precluded us from evaluating the EAR, considering the delivered energy instead of the prescribed energy. This may explain the higher values of EAR observed in our study, regardless of PP, in comparison with the available data in the literature discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP-sensitive potassium channels increase in case of endotoxemia and are also involved in the pathogenesis of alveolar epithelial barrier failure, explaining the importance of potassium in the ARDS [ 25 , 26 ]. Fu et al reported that high body temperature, high systolic blood pressure, and diabetes were not associated with the development of ARDS [ 27 ]. Our results were consistent with those reported in available studies.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptual model for the development of the NUTRIC score incorporated predictor markers of acute starvation, chronic starvation, acute inflammation, and chronic inflammation [ 22 ]. In contrast to many widely used nutritional risk assessments, this score was developed specifically for use in patients admitted to the intensive care unit [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. One potential drawback of the mNUTRIC score originates from the characteristics of the study group that were used to develop the score; the study was based on a relatively small group (n = 597) consisting mainly of Caucasian patients (90%) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%